Study on the level of understanding in students of Diploma in Muamalat and Halal Management of ACIS semester five UiTM about ETiQa Takaful Maybank / Muhammad Mirza Akmal Rusdi - Rusdi, Muhammad Mirza Akmal (2019)
While Islamic finance industry has witnessed a tremendous growth across the globe, one of the markets, Takaful, still requires attention in order to strengthen their position in the industry as well to increase their market share over their conventional counterparts. However, there are still many people who do not know nor learn about one of Muamalat's knowledge. The use of the Takaful concept facilitates the inevitable affairs of a person. Furthermore, many still do not know about the laws related to this Takaful knowledge. This study was aimed to study the level of understanding of Muamalat & Halal diploma students in the 5th semester of the Contemporary Islamic Studies Academy (ACIS) of Puncak Alam Institute of Technology Mara (UiTM) on eTiQa Takaful. Furthermore, the findings show that the level of knowledge of students in Academy of Contemporary of Islamic Studies on eTiQa Takaful Maybank are on average.